Acute Antegrade TAVI Migration Successfully Treated with Snare Utilization and Near Valve-in-Valve (Viv) Implantation - Tsanaxidis, Nikolaos; Wrigley, Benjamin; Cotton, James; Balakrishnan, Deepu (Cardiology and Cardiovascular Medicine, 2022)
90-year-old woman admitted urgently in Cardiology ward at New Cross with acute heart failure symptoms on background of severe aortic stenosis. Also reported previous syncopal episodes. On admission echocardiogram performed which revealed aortic valve area of 0.48 cm2 and mean pressure gradient of 41mmHg. Her Left Ventricular Ejection Fraction was 35%. After stabilizing her with diuresis, she underwent computed tomography TAVI workup.This revealed reasonable ilio-femoral access and estimation of valvular annular size undertaken. Trans-catheter aortic valve implantation eventually took place. Ultrasound guidance used to gain access.6Fr sheath inserted into left femoral artery (graduated pigtail for aortogram),7Fr into left femoral vein (temporary pacing wire) and 6Fr into right femoral artery (RFA) which was pre-closed with 2 Proglides and upgraded to 9Fr sheath. Immediately,the aortic valve crossed in conventional manner and a 26mm Medtronic Evolut pro was implanted [1]. Unfortunately post release the valve migrated into ascending aorta,with pendular movements in an aneurysmal aorta [2]. As the patient was haemodynamically stable we implanted a larger valve after snaring the 26 Pro.A 9Fr long sheath inserted into RFA and an EN Snare (Merit Medical) used successfully to snare the migrated valve [3,4]. A 6Fr sheath introduced into the left radial artery (LRA) and graduated pigtail was inserted through there for landmarks. The aortic valve was re-crossed sequentially and a 29mm Evolut R manoeuvred carefully through first valve and implanted whilst pacing[5,6]. Further postdilatation with 26mm VACS 2 balloon (Osypka) at the annular and supra-annular level to expand the valve to optimal size [7]. Final result was satisfactory with at most mild AR [8].